Considering Young People’s Dislocation From STEM Education: Looking Beyond the Narrow Focus of Teaching and Learning Practice Within School - Fraser, Sharon; Barnes, Nicoli; Kilpatrick, Sue; Guenther, John; Nutton, Georgie (Frontiers in Education, 2021)
Rural, regional and remote (RRR) communities and industries in Australia cannot currently produce or attract the workforce needed to survive, making skills and qualifications in science, technology, engineering and mathematics (STEM) increasingly important (Houghton, 2019). Yet student engagement in STEM education in RRR schools remains low, with limited numbers of young people either moving into further STEM education post-secondary (Halsey, 2018), or accessing readily available STEM-related jobs in RRR areas. Currently many rural children and young people are not exposed to, nor recognize the diverse ways in which STEM knowledge is required and used in their world (Avery, 2013). We propose that if young people are to increasingly engage with STEM and continue onto STEM-related careers, they must be able to see connections between their ‘school’ learning of STEM and the STEM knowledge that is enacted in rural work and life (Avery, 2013). We also suggest that for this to change, there should be increased visibility of ‘place-based’ knowledges, including Aboriginal STEM knowledges, in RRR communities to promote enhanced student engagement with STEM. In this paper we explore these ideas by drawing on Foucauldian (1972) and Bordieuan (1977) understandings to develop a methodological framework – the Place-based STEM- alignment Framework for the purposes of exposing alternate STEM knowledges. We argue that the nuanced and critical methodological approach applied in the development of the Place-based STEM-alignment Framework, is necessary in order to generate this analytical tool and provide data that will allow us the scope to ‘reset’ current understandings of STEM knowledges. The framework design provides us with the methodological vehicle to identify possible reasons for the invisibility of STEM knowledge and practices in the local fabric of RRR communities and to examine enablers and/or barriers to engagement in STEM learning. The framework must be a practical tool, one that can be used in RRR communities to engage, children and young people, in STEM, in a way that is meaningful and that aligns with their everyday experience of RRR life. Finally, the framework has to work to enable alternative perspectives to be exposed that will advance methodological considerations of STEM.